A New Echinocaridid Phyllocaridan from the Lower Devonian of Central-Eastern Poland. Issue 6 (1st November 2015) - Mazurek, Dawid; Dec, Marek; Łukowiak, Magdalena
Abstract: A new specimen of a basal echinocaridid phyllocaridan is noted from the Lower Devonian sediments of the Izdebno IG-1 borehole of central-eastern Poland. The description and reconstruction are based on a three-dimensionally preserved incomplete left carapace valve. The unique characters of the valve surface, mainly in the form of the number and location of nodes, places this specimen within Ptychocaris . However, the unique arrangement of nodes on its carapace allows us to erect a new species, Ptychocaris sheldoni n. sp. The parallel and longitudinal ridges ('striae') preserved on the carapace suggest the ability of a fast burial into the muddy seafloor.